2021
DOI: 10.3389/fonc.2021.643654
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Data on Apatinib Efficacy - Results of a Retrospective Study in Metastatic Breast Cancer Patients Pretreated With Multiline Treatment

Abstract: ObjectivesThe NCCN guidelines recommend that the addition of bevacizumab should be considered in metastatic breast cancers in some circumstances, but there are no recommendations for the similar antiangiogenic drug apatinib. The aim of this study was to evaluate the safety and efficacy of apatinib in metastatic breast cancer patients pretreated with multiline treatment in a real-world setting.Materials and MethodsMetastatic breast cancer patients pretreated with multiline treatment who had apatinib treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Previous research has shown that apatinib, an independently developed anticancer drug in China, competitively binds to the tyrosine ATP-binding site in the receptor cell and exerts an inhibitory effect on tumor angiogenesis. It is an oral antiangiogenesis-targeting drug that blocks VEGFR-2, thereby reducing the activation of mitogenic protein kinase (MAPK) and plays an antitumor role in inhibiting the proliferation of vascular endothelial cells in a variety of solid malignancies [20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that apatinib, an independently developed anticancer drug in China, competitively binds to the tyrosine ATP-binding site in the receptor cell and exerts an inhibitory effect on tumor angiogenesis. It is an oral antiangiogenesis-targeting drug that blocks VEGFR-2, thereby reducing the activation of mitogenic protein kinase (MAPK) and plays an antitumor role in inhibiting the proliferation of vascular endothelial cells in a variety of solid malignancies [20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…We still included this study because the proportion of patients without meeting the inclusion criteria was low. Finally, six studies were included and deemed eligible for further quality evaluation and analysis ( 7 9 , 14 , 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Apatinib is a small-molecule tyrosine kinase inhibitor (TKI) that selectively binds to and inhibits VEGFR-2 ( 7 ). In 2014, two phase II clinical trials demonstrated the objective efficacy results and acceptable toxicity in pretreated metastatic TNBC and non-TNBC patients ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“… 24 In addition, results from a retrospective study, which investigated the antitumor activity and safety of apatinib combined with chemotherapy in 66 pretreated advanced breast cancer patients, revealed that the median PFS and OS were 6.0 months and 10.0 months, respectively. 47 Another observational study analyzed the efficacy and safety of apatinib combined with chemotherapy in 85 patients with previously treated advanced breast cancer, and concluded that the median PFS and OS in the TNBC group were 5.2 months and 11.4 months, respectively, while the median PFS and OS in the non-TNBC group were 4.3 months and 11.3 months, respectively. 48 In consideration of the efficacy of apatinib in advanced TNBC, our study aimed to evaluate the efficacy and safety of neoadjuvant apatinib combined with standard chemotherapy for early-stage TNBC patients.…”
Section: Discussionmentioning
confidence: 99%